Self‐Reported Function More Informative than Frailty Phenotype in Predicting Adverse Postoperative Course in Older Adults. Issue 11 (19th September 2017) - Kapoor, Alok; Matheos, Theofilos; Walz, Matthias; McDonough, Christine; Maheswaran, Abiramy; Ruppell, Evan; Mohamud, Deeqo; Shaffer, Nicholas; Zhou, Yanhua; Kaur, Shubjeet; Heard, Stephen; Crawford, Sybil; et al.
Abstract : Background/Objective: Current preoperative assessment tools such as the American College of Surgeons Surgical Risk Calculator (ACS Calculator) are suboptimal for evaluating older adults. The objective was to evaluate and compare the performance of the ACS Calculator for predicting risk of serious postoperative complications with the addition of self‐reported physical function versus a frailty score. Design: Prospective cohort. Setting: Two tertiary care academic medical centers in Massachusetts. Participants: Individuals aged 65 and older undergoing any surgery with a risk of serious complication of 5% or greater (N = 403). Measurements: We measured self‐reported physical function using the Late‐Life Function and Disability Instrument (LLFDI FUNCTION) and frailty phenotype (FP), which has a score ranging from 0 to 5 based on slow gait speed, weak handgrip, exhaustion, weight loss, or low activity. Using c‐statistic and net classification improvement (NRI), we then analyzed capability of LLFDI‐FUNCTION versus FP to improve the ACS Calculator for predicting an adverse postoperative course (serious complication, discharge to nursing home, readmission, death within 30 days of surgery). Increase in c‐statistic and net reclassification improvement (NRI) for LLFDI‐FUNCTION versus FP in addition to the ACS Calculator for predicting an adverse postoperative course (serious complication, discharge to nursing home, readmission, death within 30 days of surgery) Results: Over 30 days, 26% of participants developed an adverse postoperative course. The increase in c‐statistic for the ACS Calculator (baseline value 0.645) was slightly greater with LLFDI‐FUNCTION (0.076) than with FP (0.058), with a bootstrapped difference in c‐statistic of 0.005 (95% confidence interval = 0.002–0.007). NRI was also better with LLFDI‐FUNCTION. Conclusion: The LLFDI‐FUNCTION predicted postoperative complications slightly better than the FP. Further studies are needed to confirm these findings and validate the use of the LLFDI‐FUNCTION with the ACS Calculator for preoperative assessments of older adults.